SOCIAL MEDIA ADVERTISING ASSISTANCE WITH PERSUASION CONCEPT – ELABORATION LIKELIHOOD MODEL (ELM) FOR SMES IN SURABAYA - Phima Ruthia Dwikesumasari; Maurisia Putri Permatasari; Damar Kristanto (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Along with the development of digital media tools, the direction of marketing shifts from conventional to social media-oriented. However, this is not easily conducted by SME business circles. Many of them do not have high literacy, do not have IT coding skills. In addition, capitalizing as well as maintaining a website are costly for them. This fact encourages the SMEs to look at another opportunity, namely the use of social media. However, it proves that these SMEs have not utilized the use of social media with persuasive advertisements. Objective: This community service activity purposes to assist the SMEs in Surabaya creating their social media advertisements using the persuasion concept-elaboration likelihood model (ELM) to solve the problems in marketing. Methods: The methods used are (1) discussion; (2) training and assisting in making advertisements; (4) evaluating/monitoring. As a result of this community service activity, the SMEs that have been assisted are able to create persuasive social media advertisements and can improve their marketing performance. Results: These MSME owners are able to create advertisements using the ELM method and determine the performance of these advertisements. Conclusion: SME owners can create advertisements using the ELM method during the training period, conduct independent evaluations of advertisements, the sales performance of these SMEs tends to increase compared to the previous by creating advertisements using the ELM method, practical modules are provided so that making advertisements using same method can be practiced for current and future needs.